John Wick [videorecording (DVD)] - Reeves, Keanu; Nyqvist, Michael, 1960-2017; Allen, Alfie, 1986-; Palicki, Adrianne, 1983-; Moynahan, Bridget, 1971-; Winters, Dean, 1964-; McShane, Ian, 1942-; Leguizamo, John; Dafoe, Willem (Lionsgate, 2015)
When sadistic young thugs senselessly attack a brilliantly lethal ex-assassin, they have no idea that they've just awakened the boogeyman. With New York City as his bullet-riddled playground, Wick embarks on a merciless rampage, hunting down his adversaries with the skill and ruthlessness that made him an underworld legend.